النّظرياتُ المُفسِّرةُ لرأس المالِ الاجتماعيّ قراءةٌ سوسيولوجيةٌ - الله, الأستاذ الدكتور ئاسو إبراهيم عبد; عباس, م.م. بروين أحمد (Sulaimani Journal for Humanities, 2023)
Social capital is one of the human beings' most important assets and needs that has an effective role in the promotion, level of lifestyle, and social development. The concept of social capital has different definitions, depending on the history of societies and scholars' fields and characteristics. Social capital is a structured social network, based on interaction, exchange, and social cooperation. It plays a role in the domain of self-confidence and adopted social values. For example, social capital dimensions affect the social structure and the social composition of society and it explains how to invest these dimensions and achieve social goals. This paper presents the theories of social capital from the perspectives of the scholars (Pierre Bourdieu, James Coleman, and Robert Putnam) who discuss the principles and the roots of social capital theory. They also see investment in social relationships as a source of social productivity. The nature and structure of relationship theory are closed and semi-opened. Social capital has many public benefits, so it is considered a public good rather than a private one, i.e. it has a more social basis. Simultaneously, it has a role in solving social problems by providing trust, self-confidence, commitment, and security for individuals and society.